Muslim community’s understanding of an Islamic inheritance will in Pulau Duyong, Kuala Terengganu, Malaysia - Basri, Ibrahim; Mohd Ali, Mohd Yusuf; Ahmad Jazlan, Mat Jusoh (IDOSI Publications, 2015)
A will is a financial management instrument after one’s death which allows the Muslims to spend some of their wealth on things that they desire after their death. It is one of the rights from the Islamic rights of inheritance that has to be carried out by the inheritors. The existence of will products as a mechanism to solve the issue of inheritance for the Muslims in Malaysia has caused some confusions about the role of a will. Therefore, this research is aimed to investigate the knowledge among the Muslim community in Pulau Duyong, Terengganu about the will as one of the Islamic rights of inheritance and its role on the deceased’s properties. This research is carried out using both qualitative and quantitative methods by means of documentation and survey forms which were distributed to the respondents in Pulau Duyong, Kuala Terengganu. The data from the field survey was descriptively analyzed with the analysis method of mean, standard deviation, percentage and mean score using the Statistical Package for Social Science (SPSS) software. This research concluded that a will is an important instrument to be carried out before the distribution of properties to the inheritors. This research also found out that the knowledge of the Muslim community in Pulau Duyong, Kuala Terengganu about the will as one of the Islamic rights of inheritence is at a medium level. In relation to that, the concept of will has to be disclosed more comprehensively among the Muslim community, so its role can be understood in a deeper sense especially when managing the distribution of inheritence.